2009
DOI: 10.1016/j.cgh.2009.03.022
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Histologic Scoring System to Evaluate Mucosal Biopsies From Patients With Eosinophilic Esophagitis

Abstract: Background and Aim-Eosinophilic esophagitis (EoE) is characterized by medically/surgicallyresistant gastroesophageal reflux symptoms and dense squamous eosinophilia. Studies suggest that histological assessment of esophageal eosinophilia alone cannot reliably separate patients with EoE from those with gastroesophageal reflux disease (GERD). Our goal was to develop an assay to identify EoE patients and perhaps differentiate EoE from other causes of esophageal eosinophilia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
153
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(166 citation statements)
references
References 19 publications
5
153
0
6
Order By: Relevance
“…The extent of eosinophil degranulation associated with the I5/hE2 model is not a function of pulmonary leukotriene-mediated events. Immunohistochemistry of lung sections using a monoclonal antibody that specifically recognizes eosinophil peroxidase (EPX [12]) demonstrated that the induced tissue eosinophilia of the parental I5/hE2 model remained unchanged in I5/hE2 mice devoid of all leukotrienes (5-LO 2/2 /I5/hE2), LTB 4 activities (BLT-1 2/2 /I5/hE2), or the blockade of cys-leukotriene-mediated events (MK/I5/hE2). Moreover, assessments of extracellular matrix-associated EPX deposition in the lungs of these animals showed that the extensive eosinophil degranulation (i.e., increased EPX) linked with the I5/hE2 model was not a function of leukotriene-mediated activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of eosinophil degranulation associated with the I5/hE2 model is not a function of pulmonary leukotriene-mediated events. Immunohistochemistry of lung sections using a monoclonal antibody that specifically recognizes eosinophil peroxidase (EPX [12]) demonstrated that the induced tissue eosinophilia of the parental I5/hE2 model remained unchanged in I5/hE2 mice devoid of all leukotrienes (5-LO 2/2 /I5/hE2), LTB 4 activities (BLT-1 2/2 /I5/hE2), or the blockade of cys-leukotriene-mediated events (MK/I5/hE2). Moreover, assessments of extracellular matrix-associated EPX deposition in the lungs of these animals showed that the extensive eosinophil degranulation (i.e., increased EPX) linked with the I5/hE2 model was not a function of leukotriene-mediated activities.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical identification of eosinophils and evidence of degranulation was performed using a monoclonal antibody recognizing EPX (12).…”
Section: Identification Of Lung-infiltrating Eosinophils and Evidencementioning
confidence: 99%
“…For example, we have demonstrated, through the use of a novel anti-eosinophil peroxidase monoclonal antibody (EPX-mAb), that this detection method was capable of identifying tissue infiltrating eosinophils in patient biopsies, as well as evidence of degranulation, that was significantly beyond the ability to do so through conventional evaluations of hematoxylin and eosin-stained slides. 83,117 In addition, biochemical assays of eosinophil activities 118 and eosinophil granule proteins have been used as novel assays to link eosinophil activities to disease severity and/or patient outcomes as is true of unique ELISA assays of eosinophil granule proteins (eg, EPX 119 ). The availability of these novel methodologies is of particular interest moving forward as the roles of eosinophils expand from the "classic" eosinophil-associated diseases of asthma and helminth infection to the myriad of diseases and pathologies linked with eosinophils.…”
Section: Eosinophils: Biomarkers In Translational Strategies Of Patiementioning
confidence: 99%
“…These findings suggest that quantification of eosinophil infiltration based on H&E staining is likely to be an underrepresentation of the magnitude of inflammation. Previous studies using esophageal tissue sections from human patients with eosinophilic esophagitis have shown that Epx mAb ‐ based IHC detects a 4‐fold higher number of eosinophils compared with H&E staining and potentially enables differentiation of difficult‐to‐diagnose eosinophilic esophagitis and gastroesophageal reflux disease 20. In another study using lung biopsy specimens from patients with acute lung injury, a >40‐fold higher sensitivity in the detection of eosinophils was achieved by IHC with Epx mAb relative to H&E‐stained sections, resulting in the identification of higher numbers of eosinophils in these patients compared with controls in whom differences using H&E staining alone were not significant 18.…”
Section: Discussionmentioning
confidence: 99%